2015
DOI: 10.1139/cgj-2014-0327
|View full text |Cite
|
Sign up to set email alerts
|

Installation of dynamically embedded plate anchors as assessed through field tests

Abstract: A dynamically embedded plate anchor (DEPLA) is a rocket-shaped anchor that comprises a removable central shaft and a set of four flukes. The DEPLA penetrates to a target depth in the seabed by the kinetic energy obtained through free-fall in water. After embedment the central shaft is retrieved leaving the anchor flukes vertically embedded in the seabed. The flukes constitute the load-bearing element as a plate anchor. This paper focuses on the dynamic installation of the DEPLA. Net resistance and velocity pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…However, for long slender FFPs, this added mass is limited to a small zone of soil at the tip and, when fully embedded in soil, at the rear of the FFP. This is sufficiently small that it may be ignored (Beard 1981, Shelton et al 2011Blake & O'Loughlin, 2015).…”
Section: Indirect Approach: Accelerometer Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for long slender FFPs, this added mass is limited to a small zone of soil at the tip and, when fully embedded in soil, at the rear of the FFP. This is sufficiently small that it may be ignored (Beard 1981, Shelton et al 2011Blake & O'Loughlin, 2015).…”
Section: Indirect Approach: Accelerometer Methodsmentioning
confidence: 99%
“…Young et al 2011;Buhler & Audibert 2012;Steiner et al 2014;Chow & Airey 2013), dynamically-installed anchors (e.g. O'Loughlin et al 2004, 2009Blake and O'Loughlin, 2015;Sabetamal et al 2016) and submarine runout impact on pipelines (e.g. Randolph and White, 2012;Sahdi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of drag resistance, F d , is essential in situations where (non-Newtonian) very soft fluidized soil is encountered at the surface of the seabed, and has been shown to be important for assessing loading from a submarine slide runout on a pipeline (Boukpeti et al 2012;Randolph and White 2012;Sahdi et al 2014). O'Loughlin et al (2013b) and Blake and O'Loughlin (2015) further showed that drag is the dominant resistance acting on a dynamically installed anchor in normally consolidated clay during initial embedment and typically to about 30 % of the penetration.…”
Section: Example Application Of Projectile Imu Datamentioning
confidence: 99%
“…13) showed an open crater and the dimensionless strength ratio at the trailing end of the embedded DEPLA follower, s u /c 0 d ¼ 6.9 (where d is the diameter of the DEPLA sleeve and c 0 is the effective unit weight of the soil), which is sufficient to maintain an open cavity above the follower O'Beirne et al 2015). Values for the drag coefficient, C d , were determined from the free fall in the water phase of the tests, which gave an average C d ¼ 0.7 (Blake and O'Loughlin 2015). The strain rate parameter was taken as b ¼ 0.08, which is typical of that measured in variable rate penetrometer testing (Low et al 2008;Lehane et al 2009) and approximates to an 18 % change in strength per log cycle change in strain rate, typical of that measured in laboratory testing (e.g., Vaid and Campenella 1977;Graham et al 1983;Lefebvre and LeBoeuf 1987).…”
mentioning
confidence: 99%